Innovation and performance in manufacturing industries: A comparison of the Nordic countries - Hans Lööf; Almas Heshmati; Rita Asplund; Svein-Olav Nåås (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
The availability of new internationally-harmonized innovation survey data collected from OECD countries has created some interesting opportunities for studying the following two key areas: (1) the determinants of innovation behavior at firm level, and (2) innovation as an important factor contributing to the economic growth. This paper looks at the relationship between innovation and productivity in Finland, Norway and Sweden at the firm level. Although these countries enjoy a high degree of political, social and cultural similarities, they differ largely from one another in their productivity growth and national innovation systems. The main objective here has been to examine how an identically-specified econometric model might work when the survey sampling and questionnaire are identical but the national data sets are estimated separately. Findings from the micro-based data in Europe known as Community Innovation Survey (CIS) data were subsequently investigated to see whether or not they contributed to explaining the presence of cross-country differences in aggregated productivity growth. Results reveal major discrepancies between the estimated firm-level results and the aggregated figures. Differences in the country regression results were investigated to see whether they were due to data errors, the econometric model, model specifications, estimation methods or unobservable country-specific effects. The tentative conclusion is that the representativeness of the respondent firms, the model specification and unobservable country-specific effects may partly account for the deviations between macro and micro levels.
Keywords: C51; D24; L60; O31; O32; 330; Community Innovation Survey; CIS; cross-country comparisons; innovation; manufacturing; firms; Innovation; Produktivität; Finnland; Norwegen; Schweden